Analisis Praktik Manajemen Kinerja Dalam Meningkatkan Kepuasan Pelanggan Pada Perusahaan Asuransi Syariah - Dwiki Wardana Syah; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze performance management practices in enhancing customer satisfaction in Sharia insurance companies. The research employs a descriptive qualitative approach, with data collected through in-depth interviews, direct observations, and document analysis. The findings reveal that implementing performance management based on Sharia values, such as transparency, fairness, and optimal service, significantly contributes to improving customer satisfaction. Strategies involving periodic performance evaluations, employee training, and proactive resolution of complaints have strengthened customer trust in the services provided. This study concludes that the integration of Sharia principles with effective performance management practices can be a key factor in achieving customer satisfaction in the Sharia insurance sector.